Vapor-permeable polymer cement waterproof coating special for outer wall and preparation method of vapor-permeable polymer cement waterproof coating

By combining modified acrylic emulsion and special cement, polymer cement waterproof coatings with high vapor permeability are formed, which solves the problem of insufficient vapor permeability of water vapor in the external insulation system of the exterior wall, reduces the risk of cracking and shedding, and increases the risk of The bonding capacity meets the water vapor permeability requirements of relevant standards.

CN119193002APending Publication Date: 2024-12-27BEIJING ORIENTAL YUHONG WATERPROOF TECH CO LTD

Patent Information

Application Number
CN202411343363.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the external insulation project of exterior walls, polymer cement waterproof coatings have cracked and fallen due to insufficient steam permeability of water vapor in the insulation system, which cannot meet the water vapor permeability requirements in the GBT 29906-2013 standard.

Method used

Use vapor permeable polymer cement waterproof coatings including modified acrylic emulsions and special cements to form a micro foaming system through emulsion dispersion and micro-reaction, and combine breathable functional materials to improve vapor permeability, and enhance adhesiveness through reaction of modified acrylic emulsions with cement. Relay ability.

Benefits of technology

The vapor permeability of polymer cement waterproof coatings is realized, the possibility of cracking and falling off of external insulation outside the exterior wall is reduced, the standard requirements for water vapor permeability is met, and the adhesion ability to the mortar base surface is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005060316330000071
    Figure BDA0005060316330000071
  • Figure BDA0005060316330000081
    Figure BDA0005060316330000081
  • Figure BDA0005060316330000091
    Figure BDA0005060316330000091
Patent Text Reader

Abstract

The invention discloses a vapor-permeable polymer cement waterproof coating special for an outer wall and a preparation method of the vapor-permeable polymer cement waterproof coating. The vapor-permeable polymer cement waterproof coating comprises a liquid material component and a powder material component, wherein the liquid material component comprises water, a modified acrylic emulsion and a first auxiliary agent; and the powder component comprises special cement, a breathable functional material and a second auxiliary agent. According to the waterproof coating disclosed by the invention, the vapor permeability of the polymer cement waterproof coating is realized on the basis of the waterproof performance, and the possibility of cracking and falling of external thermal insulation of an outer wall caused by moisture in a thermal insulation system is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building waterproofing, and more specifically, relates to a special vapor-permeable polymer cement waterproof coating for exterior walls and a preparation method thereof. Background Art

[0002] Polymer cement waterproof coatings are widely used in indoor bathrooms, exterior walls and other engineering parts due to their good waterproof properties, good adhesion to concrete bases, and high cost-effectiveness. However, in recent years, the use of polymer cement waterproof coatings in exterior wall insulation projects has caused hollowing of exterior finishes and peeling of wall skins. This is mainly due to the change in the temperature difference between indoor and outdoor, which will form a water vapor partial pressure difference. The indoor water vapor will penetrate through the wall and insulation layer to the outdoors (complete the mass transfer), but it will be greatly hindered at the condensation interface of the insulation layer and cannot be transmitted. It has to accumulate at the condensation interface, causing the insulation material to be damp. The water content of the external insulation system is an important indicator related to the service life of the external insulation system. When the water content of polymer mortar is high, its bonding strength will be greatly reduced, which is easy to cause delamination, thereby causing the external insulation system to crack. In the case of freezing, this phenomenon will be aggravated. The key to solving this problem is to reduce the generation of condensed water, which requires giving the entire external insulation system vapor permeability so that water vapor can be discharged out of the system. According to the standard GBT 29906-2013 "Molded polystyrene board thin plastering exterior wall insulation system materials", the water vapor permeability wet flow density index of the molded board external insulation system should not be less than 0.85g / m 2 ·h requirement, while the vapor permeability of polymer cement waterproof coatings on the market cannot reach this value at all. Therefore, in order to solve the problems currently occurring in exterior wall projects, a vapor permeable polymer cement waterproof coating is urgently needed to meet the application of the project. Summary of the invention

[0003] The purpose of the present invention is to provide a vapor-permeable polymer cement waterproof coating specially used for exterior walls and a preparation method thereof. The waterproof coating of the present invention realizes the vapor-permeability of the polymer cement waterproof coating on the basis of the waterproof performance, thereby reducing the possibility of cracking and falling off of the exterior wall insulation caused by moisture in the insulation system.

[0004] In order to achieve the above-mentioned object, one aspect of the present invention provides a vapor-permeable polymer cement waterproof coating for exterior walls, the vapor-permeable polymer cement waterproof coating comprising: a liquid component and a powder component;

[0005] Wherein, the liquid material components include: water, modified acrylic emulsion and a first auxiliary agent;

[0006] The powder components include: special cement, air-permeable functional material and a second auxiliary agent.

[0007] According to the present invention, preferably, the liquid material components include: 5-50 parts by weight of water, 50-95 parts by weight of modified acrylic emulsion and 0.2-1.1 parts by weight of the first auxiliary agent;

[0008] The powder components include: 20-70 parts by weight of special cement, 10-80 parts by weight of air-permeable functional material and 0.4-1.2 parts by weight of a second auxiliary agent.

[0009] According to the present invention, preferably, the modified acrylic emulsion is prepared by a method comprising the following steps:

[0010] (1) emulsifying and dispersing an acrylic emulsion and an oxidant to obtain a pre-dispersion A;

[0011] (2) dissolving methacrylic acid in water, then adding sodium dodecyl sulfate for emulsification, and then adding a reducing agent and stirring to mix uniformly to obtain a pre-dispersion B;

[0012] (3) While maintaining stirring, add the pre-dispersion A to the reaction kettle, stir and mix, then dropwise add the pre-dispersion B, add a coupling agent after the dropwise addition, and then dropwise add an ethanol solution of butyl orthosilicate, continue to stir and mix after the dropwise addition, and obtain the modified acrylic emulsion.

[0013] According to the present invention, preferably, in step (1), the amount of the acrylic emulsion is 80-100 parts, and the amount of the oxidant is 0.5-2 parts by weight;

[0014] In step (2), the amount of water used is 0.5-10 parts by weight, the amount of methacrylic acid used is 1-10 parts by weight, the amount of sodium dodecyl sulfate used is 0.01-0.5 parts by weight, and the amount of reducing agent used is 0.3-1 parts by weight;

[0015] In step (3), by weight, the amount of pre-dispersion A is 90-110 parts, the amount of pre-dispersion B is 1-3 parts, the amount of coupling agent is 0.3-3 parts, and the amount of ethanol solution of butyl orthosilicate is 2-10 parts;

[0016] Preferably, in step (3), the temperature of the reaction in the reactor is controlled to be 34-36° C.; the pre-dispersion A is added to the reactor and stirred and mixed for 10-15 min; the pre-dispersion B is added dropwise for 0.5 to 1 h; an ethanol solution of butyl orthosilicate is added dropwise for 0.5 to 1 h; and the stirring and mixing is continued for 1 to 2 h.

[0017] According to the present invention, preferably, the acrylic emulsion is selected from at least one of styrene-acrylic emulsion, butyl-acrylic emulsion, pure acrylic emulsion and acetic acid-acrylic emulsion;

[0018] The mass concentration of the ethanol solution of butyl orthosilicate is 85-95%;

[0019] The oxidant is selected from at least one of hydrogen peroxide, sodium peroxide, peracetic acid and tert-butyl hydroperoxide;

[0020] The reducing agent is selected from at least one of sodium bisulfite, vitamin C, oxalic acid and sodium borohydride;

[0021] The coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, n-butyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0022] According to the present invention, preferably, the special cement is selected from at least one of P.O42.5 cement, P.O52.5 cement, P.O62.5 cement, P.C52.5 cement and P.O52.5R cement.

[0023] According to the present invention, preferably, the air-permeable functional material is selected from at least one of porous calcium carbonate, porous quartz powder, porous zeolite powder and carbon nanotubes;

[0024] Preferably, the particle sizes of the porous calcium carbonate, porous quartz powder and porous zeolite powder are independently 300-2000 meshes; and the particle size of the carbon nanotubes is 1-50 nm.

[0025] According to the present invention, preferably, the first auxiliary agent and the second auxiliary agent are each independently selected from at least one of a defoamer, a dispersant, a preservative and a thickener;

[0026] The defoamer is preferably selected from at least one of a mineral oil defoamer, a silicone defoamer and a polyether defoamer;

[0027] The dispersant is preferably selected from at least one of polycarboxylic acid sodium salt, sodium tripolyphosphate and fatty acid polyethylene glycol ester;

[0028] The preservative is preferably selected from at least one of benzimidazole esters, isothiazolinones and benzisothiazolinones;

[0029] The thickener is preferably selected from at least one of a polyurethane thickener, an alkali swelling thickener and a cellulose ether.

[0030] In the present invention, the defoaming agents used in the first auxiliary agent and the second auxiliary agent may be the same or different, the dispersants used in the first auxiliary agent and the second auxiliary agent may be the same or different, the preservatives used in the first auxiliary agent and the second auxiliary agent may be the same or different, and the thickeners used in the first auxiliary agent and the second auxiliary agent may be the same or different.

[0031] In the present invention, preferably, in parts by weight, the first auxiliary agent includes: 0.1-0.3 parts of a defoamer, 0-0.2 parts of a dispersant, 0.1-0.2 parts of a preservative and 0-0.4 parts of a thickener.

[0032] In parts by weight, the first auxiliary agent includes: 0.2-0.4 parts of defoaming agent, 0.2-0.4 parts of dispersant, 0-0.2 parts of preservative and 0-0.2 parts of thickener.

[0033] According to the present invention, preferably, the mass ratio of the liquid component to the powder component is 1:(2-3).

[0034] In the present invention, the liquid component and the powder component are mixed in a mass ratio of 1:(2-3) during use.

[0035] Another aspect of the present invention provides a method for preparing the above-mentioned waterproof coating, the preparation method comprising:

[0036] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0037] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0038] The technical solution of the present invention has the following beneficial effects:

[0039] 1. The waterproof coating of the present invention realizes the vapor permeability of polymer cement waterproof coating on the basis of waterproof performance, thereby reducing the possibility of cracking and falling off of external wall insulation caused by moisture in the insulation system.

[0040] 2. The present invention prepares a modified acrylic emulsion by organic-inorganic composite technology, grafts inorganic matter onto the side chain structure of organic matter, and forms an emulsion with a vapor permeability function. The emulsion has excellent vapor permeability.

[0041] 3. The present invention forms a micro-foaming system by micro-reaction of excess oxidant in the system with cement, and forms micron pores during the film-forming process. At the same time, air-permeable functional materials are introduced into the powder system to further increase the number of nanopores and further improve the air permeability of the system.

[0042] 4. The hydrolysis products of butyl orthosilicate and coupling agent in the modified acrylic emulsion of the present invention are coated on the mortar surface and react with calcium hydroxide and tricalcium silicate in cement to improve the bonding ability with the mortar base surface.

[0043] 5. The production process of the present invention is simple and easy to control, green and environmentally friendly, and the two components have good storage stability.

[0044] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0045] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0046] The present invention is further described below by examples:

[0047] In the following examples and comparative examples, the modified acrylic emulsion used was prepared by the following method 1 or method 2:

[0048] Method 1: (1) emulsifying and dispersing 100 parts by weight of acrylic emulsion and 1 part by weight of oxidant to obtain a pre-dispersion A;

[0049] (2) dissolving 5 parts by weight of methacrylic acid in 1 part by weight of water, then adding 0.2 parts by weight of sodium dodecyl sulfate for emulsification, and then adding 0.4 parts by weight of a reducing agent and stirring and mixing to obtain a pre-dispersion B;

[0050] (3) While maintaining stirring, add 101 parts by weight of pre-dispersion A to the reaction kettle, stir and mix for 13 minutes, then drop 2 parts by weight of pre-dispersion B for 1 hour, add 0.6 parts by weight of coupling agent, then drop 4 parts by weight of 90% butyl orthosilicate ethanol solution for 1 hour, continue stirring and mixing for 2 hours, and obtain the modified acrylic emulsion. The reaction temperature in the reaction kettle is controlled to be 35°C.

[0051] Method 2: (1) emulsifying and dispersing 90 parts by weight of acrylic emulsion and 0.8 parts by weight of oxidant to obtain a pre-dispersion A;

[0052] (2) dissolving 2 parts by weight of methacrylic acid in 0.5 parts by weight of water, then adding 0.1 parts by weight of sodium dodecyl sulfate for emulsification, and then adding 0.5 parts by weight of a reducing agent and stirring and mixing to obtain a pre-dispersion B;

[0053] (3) While maintaining stirring, add 90.8 parts by weight of pre-dispersion A to the reaction kettle, stir and mix for 13 minutes, then drop 1.5 parts by weight of pre-dispersion B for 1 hour, add 0.4 parts by weight of coupling agent, then drop 3 parts by weight of 90% butyl orthosilicate ethanol solution for 1 hour, continue stirring and mixing for 2 hours, and obtain the modified acrylic emulsion. The reaction temperature in the reaction kettle is controlled to be 36°C.

[0054] Among them, in method one and method two, the acrylic emulsion used is styrene acrylic emulsion, specifically Polycarbazine 6550; the oxidant is hydrogen peroxide; the reducing agent is sodium bisulfite; and the coupling agent is γ-aminopropyltriethoxysilane.

[0055] In the following embodiments and comparative examples:

[0056] The particle sizes of the porous calcium carbonate, porous quartz powder and porous zeolite powder used are independently 300-500 meshes; the particle size of the carbon nanotube used is 10-20 nm.

[0057] Example 1

[0058] This embodiment provides a special vapor permeable polymer cement waterproof coating for exterior walls, and the specific formula is as follows:

[0059] Liquid components: 15 parts by weight of water, 85 parts by weight of modified acrylic emulsion prepared by method 1, 0.2 parts by weight of dispersant fatty acid polyethylene glycol ester, 0.2 parts by weight of mineral oil defoamer and 0.2 parts by weight of preservative isothiazolinone;

[0060] Powder components: 50 parts by weight of P.O42.5 white cement, 50 parts by weight of porous calcium carbonate, 0.2 parts by weight of mineral oil defoamer and 0.2 parts by weight of dispersant polycarboxylate sodium salt.

[0061] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0062] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0063] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0064] The above coatings were mixed at a mass ratio of liquid: powder = 10:23, and the curing conditions were referred to Type III products in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor transmission rate in Table 1 were tested according to the test method described in Type III products in GB / T 23445-2009. The water vapor transmission rate was tested according to the test method of GB / T17146-2015 (test condition is B). The results are shown in Table 1.

[0065] Table 1 Full test data of Example 1

[0066]

[0067] Example 2

[0068] This embodiment provides a special vapor permeable polymer cement waterproof coating for exterior walls, and the specific formula is as follows:

[0069] Liquid components: 20 parts by weight of water, 80 parts by weight of the modified acrylic emulsion prepared by method 1, 0.1 parts by weight of a polyurethane thickener, 0.2 parts by weight of a polyether defoamer, and 0.2 parts by weight of a preservative benzisothiazolinone;

[0070] Powder components: 40 parts by weight of P.O52.5 gray cement, 57 parts by weight of porous zeolite powder, 3 parts by weight of carbon nanotubes, 0.3 parts by weight of silicone defoamer, 0.4 parts by weight of dispersant sodium tripolyphosphate and 0.1 parts by weight of cellulose ether thickener.

[0071] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0072] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0073] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0074] The above coatings were mixed at a mass ratio of liquid: powder = 10:23, and the curing conditions were referred to the Type III product in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor permeability in Table 1 were tested with reference to the test method described in Type III product in GB / T 23445-2009. The water vapor permeability was tested according to the test method of GB / T17146-2015 (test condition B). The results are shown in Table 2.

[0075] Table 2 Full test data of Example 2

[0076]

[0077]

[0078] Example 3

[0079] This embodiment provides a special vapor permeable polymer cement waterproof coating for exterior walls, and the specific formula is as follows:

[0080] Liquid components: 30 parts by weight of water, 70 parts by weight of the modified acrylic emulsion prepared by method 2, 0.2 parts by weight of dispersant polycarboxylate sodium salt, 0.1 parts by weight of organosilicon defoamer and 0.1 parts by weight of preservative benzimidazole ester;

[0081] Powder components: 20 parts by weight of P.O62.5 gray cement, 75 parts by weight of porous quartz powder, 5 parts by weight of carbon nanotubes, 0.2 parts by weight of dispersant polycarboxylate sodium salt, 0.3 parts by weight of polyether defoaming agent and 0.1 parts by weight of thickener cellulose ether.

[0082] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0083] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0084] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0085] The above coatings were mixed at a mass ratio of liquid: powder = 10:23, and the curing conditions were referred to Type III products in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor transmission rate in Table 1 were tested according to the test method described in Type III products in GB / T 23445-2009. The water vapor transmission rate was tested according to the test method of GB / T17146-2015 (test condition is B). The results are shown in Table 3.

[0086] Table 3 Full test data of Example 3

[0087]

[0088]

[0089] Example 4

[0090] This embodiment provides a special vapor permeable polymer cement waterproof coating for exterior walls, and the specific formula is as follows:

[0091] Liquid components: 15 parts by weight of water, 85 parts by weight of the modified acrylic emulsion prepared by method 1, 0.1 parts by weight of dispersant fatty acid polyethylene glycol ester, 0.2 parts by weight of mineral oil defoamer and 0.2 parts by weight of preservative isothiazolinone;

[0092] Powder components: 25 parts by weight of P.O52.5R white cement, 75 parts by weight of porous zeolite powder, 0.2 parts by weight of dispersant polycarboxylate sodium salt and 0.2 parts by weight of organosilicon defoaming agent.

[0093] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0094] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0095] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0096] The above coatings were mixed at a mass ratio of liquid: powder = 10:23, and the curing conditions were referred to Type III products in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor permeability in Table 1 were tested with reference to the test method described in Type III products in GB / T 23445-2009. The water vapor permeability was tested according to the test method of GB / T17146-2015 (test condition B). The results are shown in Table 4.

[0097] Table 4: Full test data of Example 4

[0098]

[0099] Example 5

[0100] This embodiment provides a special vapor permeable polymer cement waterproof coating for exterior walls, and the specific formula is as follows:

[0101] Liquid components: 7 parts by weight of water, 93 parts by weight of the modified acrylic emulsion prepared by method 2, 0.1 parts by weight of dispersant sodium tripolyphosphate, 0.2 parts by weight of mineral oil defoamer and 0.2 parts by weight of preservative benzisothiazolinone;

[0102] Powder components: 40 parts by weight of P.O52.5 white cement, 60 parts by weight of porous calcium carbonate powder, 0.4 parts by weight of dispersant polycarboxylate sodium salt, 0.4 parts by weight of mineral oil defoamer and 0.2 parts by weight of thickener cellulose ether.

[0103] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0104] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0105] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0106] The above coatings were mixed at a mass ratio of liquid: powder = 10:25, and the curing conditions were referred to Type III products in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor permeability in Table 1 were tested with reference to the test method described in Type III products in GB / T 23445-2009. The water vapor permeability was tested according to the test method of GB / T17146-2015 (test condition B). The results are shown in Table 5.

[0107] Table 5: Full test data of Example 5

[0108]

[0109] Example 6

[0110] This embodiment provides a special vapor permeable polymer cement waterproof coating for exterior walls, and the specific formula is as follows:

[0111] Liquid components: 5 parts by weight of water, 95 parts by weight of modified acrylic emulsion prepared by method 2, 0.1 parts by weight of dispersant fatty acid polyethylene glycol ester, 0.3 parts by weight of mineral oil defoamer, 0.2 parts by weight of preservative isothiazolinone and 0.4 parts by weight of alkali swelling thickener;

[0112] Powder components: 60 parts by weight of P.O42.5 gray cement, 38 parts by weight of porous quartz powder, 2 parts by weight of carbon nanotubes, 0.4 parts by weight of dispersant polycarboxylate sodium salt, 0.2 parts by weight of silicone defoamer and 0.1 parts by weight of thickener cellulose ether.

[0113] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0114] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0115] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0116] The above coatings were mixed at a mass ratio of liquid: powder = 10:25, and the curing conditions were referred to the Type III product in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor permeability in Table 1 were tested with reference to the test method described in Type III product in GB / T 23445-2009. The water vapor permeability was tested according to the test method of GB / T17146-2015 (test condition B). The results are shown in Table 6.

[0117] Table 6 Full test data of Example 6

[0118]

[0119]

[0120] Comparative Example 1

[0121] This comparative example provides a polymer cement waterproof coating for exterior walls. The difference between this comparative example and the formula of Example 5 is only that 93 parts by weight of the modified acrylic emulsion in the liquid material is replaced with 93 parts by weight of Lijia 6550 styrene acrylic emulsion;

[0122] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0123] Evenly mixing the water, styrene-acrylic emulsion and the first auxiliary agent to obtain the liquid component;

[0124] The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

[0125] The above coatings were mixed at a mass ratio of liquid: powder = 10:25, and the curing conditions were referred to Type III products in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor permeability in Table 1 were tested with reference to the test method described in Type III products in GB / T 23445-2009. The water vapor permeability was tested according to the test method of GB / T17146-2015 (test condition B). The results are shown in Table 7.

[0126] Table 7 Comparative Example 1 Full Item Test Data

[0127]

[0128]

[0129] Comparative Example 2

[0130] This comparative example provides a polymer cement waterproof coating for exterior walls. The difference between this comparative example and the formula of Example 5 is only that 38 parts by weight of porous quartz powder and 2 parts by weight of carbon nanometers in the powder are replaced with 40 parts by weight of ordinary quartz powder with a mesh size of 300-500;

[0131] The specific preparation method of the above-mentioned vapor-permeable polymer cement waterproof coating for exterior walls is as follows:

[0132] The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component;

[0133] The special cement, common quartz powder and the second auxiliary agent are mixed evenly to obtain the powder component.

[0134] The above coatings were mixed at a mass ratio of liquid: powder = 10:25, and the curing conditions were referred to the Type III product in GB / T23445-2009. The dry film thickness was 1.5 mm for comprehensive performance testing. Among them, the test items except water vapor permeability in Table 1 were tested with reference to the test method described in Type III product in GB / T 23445-2009. The water vapor permeability was tested according to the test method of GB / T17146-2015 (test condition B). The results are shown in Table 8.

[0135] Table 8 Comparative Example 2 Full Item Test Data

[0136]

[0137]

[0138] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A vapor-permeable polymer cement waterproof coating for exterior walls, characterized in that: The vapor permeable polymer cement waterproof coating comprises: a liquid component and a powder component; Wherein, the liquid material components include: water, modified acrylic emulsion and a first auxiliary agent; The powder components include: special cement, air-permeable functional material and a second auxiliary agent.

2. The waterproof coating according to claim 1, wherein: The liquid material components include: 5-50 parts by weight of water, 50-95 parts by weight of modified acrylic emulsion and 0.2-1.1 parts by weight of the first auxiliary agent; The powder components include: 20-70 parts by weight of special cement, 10-80 parts by weight of air-permeable functional material and 0.4-1.2 parts by weight of a second auxiliary agent.

3. The waterproof coating according to claim 1 or 2, wherein: The modified acrylic emulsion is prepared by a method comprising the following steps: (1) emulsifying and dispersing an acrylic emulsion and an oxidant to obtain a pre-dispersion A; (2) dissolving methacrylic acid in water, then adding sodium dodecyl sulfate for emulsification, and then adding a reducing agent and stirring to mix uniformly to obtain a pre-dispersion B; (3) While maintaining stirring, add the pre-dispersion A to the reaction kettle, stir and mix, then dropwise add the pre-dispersion B, add a coupling agent after the dropwise addition, and then dropwise add an ethanol solution of butyl orthosilicate, continue to stir and mix after the dropwise addition, and obtain the modified acrylic emulsion.

4. The waterproof coating according to claim 3, wherein: In step (1), the amount of the acrylic emulsion is 80-100 parts by weight, and the amount of the oxidant is 0.5-2 parts by weight; In step (2), the amount of water used is 0.5-10 parts by weight, the amount of methacrylic acid used is 1-10 parts by weight, the amount of sodium dodecyl sulfate used is 0.01-0.5 parts by weight, and the amount of reducing agent used is 0.3-1 parts by weight; In step (3), by weight, the amount of pre-dispersion A is 90-110 parts, the amount of pre-dispersion B is 1-3 parts, the amount of coupling agent is 0.3-3 parts, and the amount of ethanol solution of butyl orthosilicate is 2-10 parts; Preferably, in step (3), the temperature of the reaction in the reactor is controlled to be 34-36° C.; the pre-dispersion A is added to the reactor and stirred for 10-15 min; the pre-dispersion B is added dropwise for 0.5-1 h; Add the ethanol solution of butyl orthosilicate dropwise for 0.5 to 1 hour; continue stirring and mixing for 1 to 2 hours.

5. The waterproof coating according to claim 3, wherein: The acrylic emulsion is selected from at least one of styrene-acrylic emulsion, butyl-acrylic emulsion, pure acrylic emulsion and acetic acid-acrylic emulsion; The mass concentration of the butyl orthosilicate ethanol solution is 85-95%; The oxidant is selected from at least one of hydrogen peroxide, sodium peroxide, peracetic acid and tert-butyl hydroperoxide; The reducing agent is selected from at least one of sodium bisulfite, vitamin C, oxalic acid and sodium borohydride; The coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, n-butyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.

6. The waterproof coating according to claim 1 or 2, wherein: The special cement is selected from at least one of P.O42.5 cement, P.O52.5 cement, P.O62.5 cement, P.C52.5 cement and P.O52.5R cement.

7. The waterproof coating according to claim 1 or 2, wherein: The air permeable functional material is selected from at least one of porous calcium carbonate, porous quartz powder, porous zeolite powder and carbon nanotubes; Preferably, the particle sizes of the porous calcium carbonate, porous quartz powder and porous zeolite powder are independently 300-2000 meshes; and the particle size of the carbon nanotubes is 1-50 nm.

8. The waterproof coating according to claim 1 or 2, wherein: The first auxiliary agent and the second auxiliary agent are each independently selected from at least one of a defoamer, a dispersant, a preservative and a thickener; The defoamer is preferably selected from at least one of a mineral oil defoamer, a silicone defoamer and a polyether defoamer; The dispersant is preferably selected from at least one of polycarboxylic acid sodium salt, sodium tripolyphosphate and fatty acid polyethylene glycol ester; The preservative is preferably selected from at least one of benzimidazole esters, isothiazolinones and benzisothiazolinones; The thickener is preferably selected from at least one of a polyurethane thickener, an alkali swelling thickener and a cellulose ether.

9. The waterproof coating according to claim 1 or 2, wherein: The mass ratio of the liquid component to the powder component is 1:(2-3).

10. The method for preparing a waterproof coating according to any one of claims 1 to 9, characterized in that: The preparation method comprises: The water, modified acrylic emulsion and the first auxiliary agent are mixed uniformly to obtain the liquid component; The special cement, the air-permeable functional material and the second auxiliary agent are mixed evenly to obtain the powder component.

Citation Information

Patent Citations

  • Soap-free microemulsion for building materials and preparation method of soap-free microemulsion

    CN107778384A

  • Polymer cement composition

    JP2005015330A

  • Water-based foamable fireproof coating composition

    JP2011105855A

  • Elastomeric Emulsion Polymers For Masonry Coatings

    US20070248837A1

Cited By

  • Breathable polymer cement waterproof coating and preparation method thereof

    CN121517970A

  • A breathable polymer cement waterproof coating and its preparation method

    CN121517970B